A new short version of the Facial expressions of emotion: Stimuli and tests (FEEST) including prototype and morphed emotional stimuli - Kuhlmann, Benedikt; Margraf, Jürgen (Frontiers in Psychology, 2023)
The ability to recognize emotions from facial expression plays an important role in social interaction. The aim of this study was to develop a short version of the FEEST (Ekman & Friesen, 1976) as a brief instrument to measure emotion recognition ability applying prototype and morphed emotional stimuli. Morphed emotional stimuli include mixed emotions. On the whole, 68 prototype and 32 morphed emotional expressions were presented to 138 participants for 1 second. A retest with 76 participants was conducted after six months. The results showed sufficient variance for the measurement of individual differences in emotion recognition ability.Accuracy varied between emotions and was highest for anger and happiness. Cronbach´s α was on average .70 for prototype and .67 for morphed stimuli. Test-retest reliability was .60 for prototype and .62 for morphed stimuli. The new short version of the FEEST is a reliable test to measure emotion recognition.